2009
DOI: 10.1128/jb.00368-09
|View full text |Cite|
|
Sign up to set email alerts
|

Site-Specific Recombination in the Cyanobacterium Anabaena sp. Strain PCC 7120 Catalyzed by the Integrase of Coliphage HK022

Abstract: The integrase (Int) of the -like coliphage HK022 catalyzes the site-specific integration and excision of the phage DNA into and from the chromosome of its host, Escherichia coli. Int recognizes two different pairs of recombining sites attP ؋ attB and attL ؋ attR for integration and excision, respectively. This system was adapted to the cyanobacterium Anabaena sp. strain PCC 7120 as a potential tool for site-specific gene manipulations in the cyanobacterium. Two plasmids were consecutively cointroduced by conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The reverse prophage excision reaction occurs between the attL and attR sites and restores the original attP and attB 13 . We have previously applied Int for genome manipulation in plants, cyanobacteria and human cells and have shown that the accessory proteins that are required in the E. coli host are dispensable in the eukaryotic milieu 14 15 16 17 18 . In the present study we developed a cancer specific binary cell expression system that is based on the hTERT promoter.…”
mentioning
confidence: 99%
“…The reverse prophage excision reaction occurs between the attL and attR sites and restores the original attP and attB 13 . We have previously applied Int for genome manipulation in plants, cyanobacteria and human cells and have shown that the accessory proteins that are required in the E. coli host are dispensable in the eukaryotic milieu 14 15 16 17 18 . In the present study we developed a cancer specific binary cell expression system that is based on the hTERT promoter.…”
mentioning
confidence: 99%
“…Bacteriophages play a crucial role in the evolution and ecology of the Cyanobacteria group, serving not only as a means of population control but also facilitating the transfer of genes between species [59]. The integrase gene is responsible for phage integration and excision of the host's chromosome [60,61]. The presence of this gene may suggest the potential ability of the prophage region identified in the genome to establish lysogenic relationships with P. brasiliensis CCIBt3594, with further analyses required to elucidate this relationship.…”
Section: Genome Assembly and Annotationmentioning
confidence: 99%